A first principle study of band structure of tetragonal barium titanate - Razak N.A.A.; Zabidi N.A.; Rosli A.N. (American Institute of Physics Inc., 2024)
Barium titanate (BaTiO3) is a perovskite crystal structure and it is well known to have many potential applications in microelectronic industry due to its high capabilities to enhance the performance of the capacitors and other energy storage devices. BaTiO3 has been reported to have a wide band gap around 3.4 eV from previous experimental studies. In theoretical studies, the analysis of the band structure of perovskite type of materials still under investigation due to high disagreement with the experimental result. The objective of this research is to investigate the band gap of the tetragonal BaTiO3 calculated using generalized gradient approximation (GGA) and hybrid functional (HSE03) with various pseudopotential methods performed by CASTEP module. The calculation using GGA show underestimation of energy band gap. However, the band gap calculated using HSE03 approximation shows an agreement with the experimental result. 2017 Author(s).